Mineral content of Cenchrus clandestinus (Hochst. ex Chiov.) Morrone, associated with Alnus acuminata (Kunth), in the Colombian tropical high-altitude areas - Obando Enriquez, Bayron Giovanny (2023)
High Andean dairy farming is characterized by intensive and inefficient management of natural resources. Its operation is based on pastures of low nutritional quality that do not cater to the essential needs of the animals for their growth and production. One way to improve pasture quality is to introduce forest species in silvopastoral arrangements. In the Colombian cold zone, a traditional agroforestry arrangement is Alnus acuminata (Kunth) with the pasture Cenchrus clandestinus (Hochst. ex Chiov.) Morrone, a herbaceous species that covers 80% of the regional forage supply. For this study, the mineral content of C. clandestinus under incidence of A acuminata was evaluated; the research was carried out in the pastures of a silvopastoral arrangement and a monoculture without forest incidence, located in the Obonuco Research Center of Agrosavia. Four treatments and three replicates were established, defined by the presence or absence of trees and cutting times at 35 and 45 days. A randomized complete block design (RCBD), analysis of variance, and Tukey's test were used to determine significant differences (p ≤ 0.05). The treatments in the pasture of the SPS were statistically superior compared to those of the monoculture of pasture without trees. There were higher levels of calcium, phosphorus, magnesium, potassium, copper, iron, and zinc in the plots of the arrangement; the system with treatment and cuts every 35 days yielded the best results. Associating A acuminata and C clandestinus had a positive effect on the pasture; silvopastoral interactions significantly improved the production and quality of the pasture.